2015
DOI: 10.1007/s00704-015-1453-7
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity study of reference crop evapotranspiration during growing season in the West Liao River basin, China

Abstract: We have analyzed the trends of reference crop evapotranspiration (ET 0 ) through the Penman-Monteith model and climate factors in the West Liao River basin using the Mann-Kendall test after removing the effect of significant lag-1 serial correlation from the time series of the data by trendfree pre-whitening. The changing characteristics of the sensitivity coefficients and the spatial distribution during growing season are investigated, and the correlation between the sensitivity coefficients with elevation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 69 publications
3
14
2
2
Order By: Relevance
“…However, in the context of current global warming, 91% of stations had ET 0 declines during the main crop growth stages, with 61% showing a decreasing trend (p < 0.05). Our assessment agreed with the finding reported by Gao et al [22], who indicated a decrease in ET 0 over the Liao River basin (part of which was in Liaoning province), despite province-wide temperature increases. This is because the decreases in wind velocity and sunshine duration over Liaoning have a higher negative impact on ET 0 than the positive impact of increased temperature [45].…”
Section: Discussionsupporting
confidence: 93%
“…However, in the context of current global warming, 91% of stations had ET 0 declines during the main crop growth stages, with 61% showing a decreasing trend (p < 0.05). Our assessment agreed with the finding reported by Gao et al [22], who indicated a decrease in ET 0 over the Liao River basin (part of which was in Liaoning province), despite province-wide temperature increases. This is because the decreases in wind velocity and sunshine duration over Liaoning have a higher negative impact on ET 0 than the positive impact of increased temperature [45].…”
Section: Discussionsupporting
confidence: 93%
“…Ye et al [32] found SD was the dominating factor, with RH, WS, and TA following in the Poyang Lake catchment. Gao et al [30] studied the sensitivities of ET ref to the climate factors in the crop growth period in West Liao River Basin, then found SR was the most sensitive factor, with RH following. Moreover, Gao et al [35] also have demonstrated SR was the most dominant factor for ET ref in the same study area at the annual time scale, but varied at the seasonal time scale.…”
Section: Impact Of Climate Factors To Et Ref Trendsmentioning
confidence: 99%
“…Prior to applying the M-K test in this study, a pre-whitening method should be employed to eliminate the effect of a serial correlation on the trend value [57]. Yue et al [58] improved this method and proposed an alternative approach, namely TFPW (trend-free pre-whitening), which is widely applied in many related study areas [17,30,59]. …”
Section: Trend Analysismentioning
confidence: 99%
“…Furthermore, the empirical or semi-empirical f studied because of the lack of measured values, and the FAO56-PM f studies over China [25][26][27][28][29][30][31][32][33] without calibration. However, the param ; (d) FAO24; (e) FAO56-PM; (f) Deng Genyun; (g) Tong Hongliang) and CERES data (h) at the nineteen radiation stations.…”
Section: Assessment Of the Existing R Nl Empirical Formulasmentioning
confidence: 99%